2006
DOI: 10.1152/ajprenal.00269.2005
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular ANG II induces cytosolic Ca2+mobilization by stimulating intracellular AT1receptors in proximal tubule cells

Abstract: Intracellular ANG II induces biological effects in nonrenal cells, but it is not known whether it plays a physiological role in renal proximal tubule cells (PTCs). PTCs express angiotensinogen, renin, and angiotensin-converting enzyme mRNAs, suggesting the presence of high levels of intracellular ANG II. We determined if microinjection of ANG II directly in single PTCs increases intracellular calcium concentration ([Ca2+]i) and, if so, elucidated the cellular mechanisms involved. Changes in [Ca2+]i responses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
111
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(123 citation statements)
references
References 40 publications
9
111
1
2
Order By: Relevance
“…This increase was prevented by a cellpermeable analog of an ETB-selective antagonist, IRL-2500, but not by adding BQ610 and BQ788 to the extracellular medium, thus confirming a direct role of nuclear ETB in regulating nuclear Ca 2+ signalling in intact ventricular myocytes. Other GPCRs found in nuclear membranes have also been show to increase [Ca 2+ ] n including Ang II [18,91], bradykinin B2 [21], prostaglandin E 2 [22][23][24], lysophosphatidic acid type-1 [25,26], and metabotropic glutamate type-5 [92][93][94][95].…”
Section: Discussionmentioning
confidence: 99%
“…This increase was prevented by a cellpermeable analog of an ETB-selective antagonist, IRL-2500, but not by adding BQ610 and BQ788 to the extracellular medium, thus confirming a direct role of nuclear ETB in regulating nuclear Ca 2+ signalling in intact ventricular myocytes. Other GPCRs found in nuclear membranes have also been show to increase [Ca 2+ ] n including Ang II [18,91], bradykinin B2 [21], prostaglandin E 2 [22][23][24], lysophosphatidic acid type-1 [25,26], and metabotropic glutamate type-5 [92][93][94][95].…”
Section: Discussionmentioning
confidence: 99%
“…37,52,63,70,71 Activation of AT 1 -receptors leads to phosphoinositide hydrolysis, mobilisation of intracellular calcium, and inhibition of adenylate cyclase. 38,45,46,57,72,73 By contrast, only low levels of AT 2 -receptors are expressed in proximal tubules and the role of this receptor is much less clearly defined than that of the AT 1 -receptor. 57,60,[74][75][76] The classic view of Ang II-mediated actions is that Ang II binds its receptors at the plasma membrane and phosphorylation of the receptor…”
Section: Overview Of Proximal Tubule Reninangiotensin Systemmentioning
confidence: 99%
“…Intracellular kinases activated by Ang II include extracellular signal-regulated protein kinase(s) (ERKs) 63,70,117,122 JAK-STAT signalling 117,123,124 and calcineurin phosphatase. 126,127 Internalised Ang II may also be translocated to the nucleus, 20,97,99,110 where it may activate nuclear calcium 28,29,45 and stimulate transcription of NHE-3 and pro-inflammatory cytokines and growth factors. 20,47,69,97,111,128 Recent studies indicate that Ang II activates nuclear transcription factor NF-ÎșB and activator protein-1 (AP-1) in the kidney, leading to longlasting inflammatory and growth-promoting effects.…”
Section: O P Y R I G H T J R a A S L I M I T E D R E P R O D U C T mentioning
confidence: 99%
“…We previously reported that intracellular administration of angiotensin II via liposomes increases contractility of rat aorta via activation of intracellular receptors (7). Similarly, microinjection of angiotensin II increases cytosolic Ca 2Ï© concentration ([Ca 2Ï© ] i ) in vascular smooth muscle cells (13,16) or kidney proximal tubule cells (49). The intracellular angiotensin II can result either via uptake from the interstitium or by intracellular synthesis.…”
mentioning
confidence: 99%